Metrics : how to improve key business results - Klubeck, Martin (Apress ; Distributed by Springer Science+Business Media, 2011)
Provides a step-by-step method for building an organizational effectiveness report card. This books shows how to: identify, collect, analyze and report metrics that will be useful for improving all aspects of the enterprise; understand the difference between data, measures, information, and metrics; develop meaningful and accurate metrics; formulate practical answers to data-related questions; select and use the proper tools for creating, implementing and using metrics.